Continued Discontinuation of TKI Treatment in Medullary Thyroid Carcinoma – Lessons From Individual Cases With Long-Term Follow-Up - Brandenburg, Tim; Tiedje, Vera; Muchalla, Philipp; Theurer, Sarah; Weber, Frank; Schmid, Kurt Werner; Dralle, Henning; Führer, Dagmar (Frontiers in Endocrinology, 2021)
The tyrosine kinase inhibitors (TKI) vandetanib and cabozantinib are approved as targeted therapies in advanced medullary thyroid carcinoma (MTC) with symptoms or high tumour burden. Only recently, toxicity in long-time TKI usage was analysed. However, little is known about the impact of TKI discontinuation on MTC disease course after longer-term therapy. Here, we report our experience in a series of 7 MTC patients with vandetanib treatment of up to 87 months followed by discontinuation for concerns of toxicity or due to side-effects. The discontinuation of TKI therapy is a relevant clinical scenario. To our knowledge we present the largest single center series on an important aspect of TKI management.